Kepercayaan sebagai Mediasi Kepuasan Pengguna Online Shopping di Indonesia - Siska Ernawati Fatimah; Ario Purdianto; Dita Septiani; Nadhira Azzhara (JKBM (JURNAL KONSEP BISNIS DAN MANAJEMEN), 2021)
The rise of services for marketplaces in Indonesia has led to changes in people's shopping patterns to meet their daily needs. The change in shopping patterns from offline to online has increased during the COVID-19 pandemic, this provides an opportunity for marketplace managers to take advantage of the use of social media to shop online to meet their needs. In addition, it spurs marketplace managers to compete to provide satisfaction to its users. The purpose of the study was to determine the role of trust as a mediating variable on the influence between online transactions and the satisfaction of active users of the Tokopedia marketplace in Indonesia, especially in the city of Cirebon. The data collection technique in this study used a questionnaire with the acidental sampling method which involved 100 active users of the Tokopedia marketplace in Cirebon City as respondents. The data analysis used is descriptive and inferential statistics, namely the Structure Equation Model using SmartPLS 3. The results of data analysis show that online transactions directly affect user satisfaction and online transactions affect user satisfaction with trust mediation